Implications Of The Council's Honoric Court's Decision For Violation Of The Republic Of Indonesia's Code Of Ethics - La Ode Risman; Suandi, Suandi (International Journal of Education, Vocational and Social Science, 2022)
Whereas in the provisions of laws and regulations as DPR Regulation No. 1 of 2015 concerning the code of ethics which emphasizes ethical enforcement actions against public officials who commit violations related to their position and can morally damage the image of state institutions. That every member of the DPR as a state official must comply with mutually agreed internal regulations as above, the provisions contain ethical sanctions that will be obtained if they are proven to have violated the law. Whereas as an ethical violation against a state or public official, in this case a member of the DPR who commits a violation, the Honorary Court of the DPR Council will conduct a hearing against the member of the DPR. Whereas the Honorary Council of the Council is an instrument of the DPR which has the authority as an ethics enforcement agency for members of the DPR who commit ethical violations. Whereas in the decision of the Council Honorary Court in the form of a decision, namely moderate sanctions and severe sanctions. The moderate sanction is in the form of transferring membership in the DPR's appendages to removal from the leadership position of the DPR while the severe sanction is in the form of temporary dismissal which can be 3 months or permanent dismissal as a member of the DPR.